2019
DOI: 10.1021/acs.biochem.9b00689
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Inhibition of Huntingtin Protein (htt) by Polyproline PPII Helices: A Potential Interaction with the N-Terminal α-Helical Region of Htt

Abstract: Huntington's disease (HD) is a genetic neurodegenerative disorder characterized by the formation of amyloid fibrils of the huntingtin protein (htt). The seventeen-residue N-terminal region of htt (Nt 17 ) has been implicated in formation of early-phase oligomeric species, which may be neurotoxic. Because tertiary interactions with a downstream (C-terminal) polyproline (polyP) region of htt may disrupt oligomer formation which are precursors to fibrillar species, the effect of co-incubation of a region of htt w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 86 publications
1
24
0
Order By: Relevance
“…Therefore, quantitative studies of the speed of aggregation were performed with constructs carrying a limiting number of glutamines (see also [83]). It should be noted that in their natural context the solubility of the full-length protein or its exon 1 domain is increased by the polyproline flanking sequence following the polyQ domain [31,32,40,48]. Therefore, as an alternative, exon 1 fragments were investigated where the carboxy-terminal proline-rich domain slows down the aggregation process, probably through interactions with polyQ and htt17 (e.g., [26,42,84]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, quantitative studies of the speed of aggregation were performed with constructs carrying a limiting number of glutamines (see also [83]). It should be noted that in their natural context the solubility of the full-length protein or its exon 1 domain is increased by the polyproline flanking sequence following the polyQ domain [31,32,40,48]. Therefore, as an alternative, exon 1 fragments were investigated where the carboxy-terminal proline-rich domain slows down the aggregation process, probably through interactions with polyQ and htt17 (e.g., [26,42,84]).…”
Section: Discussionmentioning
confidence: 99%
“…Recent structural investigations reveal high conformational plasticity of htt17 and the subsequent polyQ domain where htt17 association [26], its interactions with the membrane [43][44][45][46][47] or with other polypeptide domains are associated with random coil-helix structural transitions [48,49]. A recent NMR study has shown that in the solution, the htt17 sequence associates in a dimer of dimers preaggregation state [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quantitative studies of the speed of aggregation were performed with constructs carrying a limiting number of glutamines (see also (73)). It should be noted that in their natural context the solubility of the full-length protein or its exon 1 domain is increased by the polyproline flanking sequence following the polyQ domain (28,29,37,44). Furthermore, in the cellular environment, interactions with other proteins, chaperones and proteases, as well as other domains of the full-length protein assure that healthy cells are protected from huntingtin aggregation (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…Once the interactions with the membrane are established the aggregation process is enhanced by high peptide density (i.e. P/L ratio) and by extended polyQ chains (Tables 2 and 3) but slowed down by the presence of the polyproline stretch that follows the poly-Q domain (44,83). Thereby these and other biophysical observations provide a rationale for a number of biochemical and cell biological experiments where huntingtin has been shown associated with membranes of intracellular organelles (6,10,13,(16)(17)(18)(19)(20)25) or where the membrane anchoring domain htt17 has been demonstrated to promote the development of the disease (6,13,26,30,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation